Analisis Kesulitan Siswa SMP dalam Menyelesaikan Soal Materi Teorema Pythagoras - Wulandari, Lila; Riajanto, Marchasan Lexbin Elvi Judah (Universitas Negeri Surabaya, 2020)
Difficulties experienced by students in learning greatly affect the achievement of student learning outcomes. This study aims to describe the results of the identification of the types of difficulties and the causes of student difficulties when solving problems based on Polya stages. This type of research is descriptive qualitative with the instrument used in written tests. The subjects of the research were 36 students of class IX at SMP Negeri 9 Cimahi. Based on the analysis that has been done, it can be concluded that the difficulties experienced by junior high school students when completing the Pythagorean theorem questions in the school are 1) difficulty understanding the problem 100%, 2) difficulty planning the completion of 40%, 3) difficulty implementing the plan 54.4%, and 4) difficulty in re-checking 76.7%. The causes of difficulties include 1) students are not accustomed to writing things that are known and asked of a problem 2) students are not accustomed to drawing conclusions from a mathematical problem 3) Concept errors because students do not understand the concept of the material. So, it is necessary to improve the learning process that prioritizes learning concepts rather than memorizing. Students must be accustomed to solving the application problems of a material. So, students will be able to solve contextual problems related to the material.